Efficacy and safety of inorganic nitrate/nitrite supplementary therapy in heart failure with preserved ejection fraction - Lv, Feng; Zhang, Junyi; Tao, Yuan (Frontiers in Cardiovascular Medicine, 2023)
Background Approximately half of patients with heart failure have a preserved ejection fraction (HFpEF). To date, only SGLT-2i, ARNi, and MRAs treatments have been shown to be effective for HFpEF. Exercise intolerance is the primary clinical feature of HFpEF. The aim of this meta-analysis was to explore the effect of inorganic nitrate/nitrite supplementary therapy on the exercise capacity of HFpEF patients. Methods We searched PubMed, Embase, Cochrane Library, OVID, and Web of Science for eligible studies for this meta-analysis. The primary outcomes were peak oxygen consumption (peak VO2), exercise time, and respiratory exchange ratio (RER) during exercise. The secondary outcomes were cardiac output, heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure, and systemic vascular resistance during rest and exercise, respectively. Results A total of eight randomized-controlled trials were enrolled for this meta-analysis. We found no benefit of inorganic nitrate/nitrite on exercise capacity in patients with HFpEF. Inorganic nitrate/nitrite compared to placebo, did not significantly increased peak VO2 (MD = 0.361, 95% CI = −0.17 to 0.89, p = 0.183), exercise time (MD = 9.74, 95% CI = −46.47 to 65.95, p = 0.734), and respiratory exchange ratio during exercise (MD = −0.003, 95% CI = −0.036 to 0.029, p = 0.834). Among the six diameters reflecting cardiac and artery hemodynamics, inorganic nitrate/nitrite can lower rest SBP, rest/exercise DBP, rest/exercise MAP, and exercise SVR, but has no effect in cardiac output and heart rate for HFpEF patients. Conclusion Our meta-analysis suggested that inorganic nitrate/nitrite supplementary therapy has no benefit in improving the exercise capacity of patients with HFpEF, but can yield a blood pressure lowering effect, especially during exercise.